Benchmarking for healthy food stores: protocol for a randomised controlled trial with remote Aboriginal and Torres Strait Islander communities in Australia to enhance adoption of health-enabling store policy and practice - Julie Brimblecombe; Megan Ferguson; Emma McMahon; Bronwyn Fredericks; Nicole Turner; Christina Pollard; Louise Maple-Brown; Joanna Batstone; Leisa McCarthy; Eddie Miles; Khia De Silva; Adam Barnes; et al. (BMC, 2024)
Abstract Background Aboriginal and Torres Strait Islander communities in remote Australia have initiated bold policies for health-enabling stores. Benchmarking, a data-driven and facilitated 'audit and feedback' with action planning process, provides a potential strategy to strengthen and scale health-enabling best-practice adoption by remote community store directors/owners. We aim to co-design a benchmarking model with five partner organisations and test its effectiveness with Aboriginal and Torres Strait Islander community stores in remote Australia. Methods Study design is a pragmatic randomised controlled trial with consenting eligible stores (located in very remote Northern Territory (NT) of Australia, primary grocery store for an Aboriginal community, and serviced by a Nutrition Practitioner with a study partner organisation). The Benchmarking model is informed by research evidence, purpose-built best-practice audit and feedback tools, and co-designed with partner organisation and community representatives. The intervention comprises two full benchmarking cycles (one per year, 2022/23 and 2023/24) of assessment, feedback, action planning and action implementation. Assessment of stores includes i adoption status of 21 evidence-and industry-informed health-enabling policies for remote stores, ii implementation of health-enabling best-practice using a purpose-built Store Scout App, iii price of a standardised healthy diet using the Aboriginal and Torres Strait Islander Healthy Diets ASAP protocol; and, iv healthiness of food purchasing using sales data indicators. Partner organisations feedback reports and co-design action plans with stores. Control stores receive assessments and continue with usual retail practice. All stores provide weekly electronic sales data to assess the primary outcome, change in free sugars (g) to energy (MJ) from all food and drinks purchased, baseline (July-December 2021) vs July-December 2023. Discussion We hypothesise that the benchmarking intervention can improve the adoption of health-enabling store policy and practice and reduce sales of unhealthy foods and drinks in remote community stores of Australia. This innovative research with remote Aboriginal and Torres Strait Islander communities can inform effective implementation strategies for healthy food retail more broadly. Trial registration ACTRN12622000596707, Protocol version 1.